The role of pH on the survival of rumen protozoa in steers - Franzolin,Raul (2010)
In order to study the effect of pH on defaunation in the rumen, four rumen fistulated steers were fed a basal roughage diet for a 4-week adaptation period followed by 17 weeks of feeding with three diets and two feeding levels of high concentrate diet. Rumen outflow fluid rate was evaluated in both ration levels. Rumen protozoa population was monitored weekly and when animals became defaunated, protozoa were reinoculated with rumen contents from one of the faunated steers. At every two weeks, during all the experimental period, rumen pH was measured in all animals at 0, 4, 8 and 12 h after feeding. It was observed an individual animal influence on the establishment and maintenance of the rumen ciliate protozoa population. In all sampling times, mean rumen pH values were higher in faunated steers than in the defaunated ones. No differences were observed in rumen outflow fluid rates between the two ration levels. Extended periods of low rumen pH are probably more detrimental to the survival of ciliate protozoa in the rumen than other factors.